The International Criminal Law in Defense of Human Rights: Looking Back at the Tip of the Iceberg - Barbosa da Cunha, Luis Emmanuel (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The challenges of human rights in the 21st century also come from a perspective based on international criminal law and the permanent International Criminal Court (ICC), as outcome of the 1998 Treaty of Rome. On the side of international criminal law, the principle of human dignity is the political ballast that lends content to internationally criminalized conduct. The International Criminal Court is the jurisdictional expression of this new branch of law. How can international criminal law contribute to the promotion and protection of human rights? It is a question of resuming a reflection made at the beginning of the 21st century. For this purpose, the bibliography and the first acts from the ICC are taken as a reference.